Quadratus lumborum block for postoperative analgesia after cesarean section: a meta-analysis of randomized controlled trials with trial sequential analysis - Zhigang Zhao (Nature Portfolio, 2021)
Abstract The aim of this study was to assess the analgesic efficacy of QLB versus controls in women undergoing cesarean section (CS). We systematically searched Cochrane Library, PUBMED, EMBASE, VIP, WANFANG, and China National Knowledge Infrastructure. Trials were eligible if parturients received QLB during CS. GRADE system was used to assess the certainty of evidence and Trial sequential analyses (TSA) were performed to determine whether the results are supported by sufficient data. Thirteen studies involving 1269 patients were included. Compared to controls, QLB significantly reduced the cumulative postoperative intravenous opioid consumption (in milligram morphine equivalents) at 24 h (MD, − 11.51 mg; 95% CI − 17.05 to − 5.96) and 48 h (MD, − 15.87 mg; 95% CI − 26.36 to − 5.38), supported by sufficient data confirmed by TSA. The postoperative pain scores were significantly reduced by QLB at 4 h, 6 h, 12 h, 24 h, and 48 h postoperatively by QLB compared with control. Moreover, the time to first request for rescue analgesic and the incidence of PONV were also significantly reduced by QLB. The quality of evidence of most results were low and moderate assessed by GRADE.